Romantic relationships in adults with ADHD: The effect of partner attachment style on relationship quality. (January 2021) - Knies, Katherine; Bodalski, Elizabeth A.; Flory, Kate
Prior literature indicates that insecure attachment styles (i.e., anxious or avoidant) and attention-deficit/hyperactivity disorder (ADHD) both have negative impacts on romantic relationships, but relatively little is known about how these factors interact among couples where one partner has ADHD and the other does not. One hundred and fifty-nine partners of adults with significant ADHD symptoms completed measures of their own attachment styles, their partner's ADHD symptoms, and relationship quality. Anxious attachment was associated with lower romantic relationship quality, but avoidant attachment was associated with more positive relationship outcomes. Results also indicated that the negative effect of ADHD symptoms on romantic relationship quality may be exacerbated by a partner's high level of anxious attachment. Though insecure attachment styles are generally thought to have a negative impact on romantic relationships, avoidant attachment was generally associated with more positive outcomes in this study. Several possible explanations based on theoretical support are included in the discussion along with clinical applications and future directions.